Overview of Knowledge, Attitude and Behaviour Level among Medical Students of Universitas Sumatera Utara towards Lactobacillus Casei Strain Shirota in Probiotic Drink - Vega Inriani; Maria Magdalena Simatupang; Nindia Sugih Arto; Dudy Aldiansyah (Sumatera Medical Journal, 2022)
Introduction. Probiotics are widely used in health research because it is considered to be beneficial for human health. Lactobacillus casei strain Shirota is one of the lactic acid bacteria which mostly found in commercial drink. This bactery can improve gut’s immunity towards pathogen by producing bacteriocin which is able to lower the pH in the gut. However it was found inappropriate probiotic product storaging, inappropriate way of consuming probiotic drink and the mixing of probiotic drink with other drinks randomly could disrupt the viability of probiotic bacteria which would reduce the benefits of the probiotic drink. Aim. The aim of this study is to observe the knowledge, attitude and behaviour level from students of faculty of medicine Universitas Sumatera Utara towards Lactobacillus casei strain Shirota in probiotic drink. Method. This is a descriptive research with cross sectional approach. The research is collecting primary data using questionnaire about knowledge, attitude and behaviour level towards Lactobacillus casei strain Shirota in probiotic drinks. Result. From 152 respondents who met all the criteria, there are 48,7% respondents have good knowledge level, 45,4% sufficient and 5,9% deficient. Moreover, there are 22,4% respondents have good attitude level, 47,4% sufficient and 30,3% deficient. Also, there are 77% respondents have good behaviour level, 21% sufficient and 2,0% deficient. Conclusion. Majority of respondents have good knowledge level, sufficient attitude level and good behaviour level towards Lactobacillus casei strain Shirota.